ChemInform Abstract: A Lewis Acid Activated Reaction of Zn with EtI to Promote Highly Enantioselective Alkyne Additions to Aldehydes. Issue 22 (15th May 2015) - Chen, Shan‐yong; Liu, Winnie; Wu, Xuedan; Ying, Jun; Yu, Xiaoqi; Pu, Lin
Abstract: The reaction of Zn with EtI is activated at room temperature by using BINOL and Ti(OiPr)4 which can then promote the highly enantioselective alkyne addition to aromatic aldehydes.